2014
DOI: 10.1002/pbc.25305
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of relation between plasma methotrexate concentration and toxicity in high‐dose methotrexate therapy of childhood nonHodgkin lymphoma

Abstract: Our results suggest that plasma MTX level is not a reliable predictor for adverse events except for nephrotoxicity in multiple HDMTX therapy courses in childhood B-NHL. Pediatr Blood Cancer 2015;62:279-284. © 2014 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…Ip et al (16) did not find an association between the blood levels of creatinine and the presence of Moderate to Severe oral mucositis during the initial period of chemotherapy. This increase was expected in blood creatinine, which previous studies have identified as a risk factor; this increase has also been shown to enhance the cytotoxicity of anticancer drugs (23)(24)(25). blood level of creatinine.…”
Section: Discussionmentioning
confidence: 61%
“…Ip et al (16) did not find an association between the blood levels of creatinine and the presence of Moderate to Severe oral mucositis during the initial period of chemotherapy. This increase was expected in blood creatinine, which previous studies have identified as a risk factor; this increase has also been shown to enhance the cytotoxicity of anticancer drugs (23)(24)(25). blood level of creatinine.…”
Section: Discussionmentioning
confidence: 61%
“…Serum methotrexate concentrations should be monitored with ongoing adjustments in hydration, alkalinization, and leucovorin rescue until the target of less than 0.05-0.1 mM is reached [1]. Plasma methotrexate monitoring is a reliable indicator specifically of nephrotoxicity but may be a limited predictor of other toxicities [59]. However, in centers where methotrexate levels cannot be monitored, assiduous monitoring of urine pH and output, serum creatinine, and twice-daily examination of mucosal membranes for evidence of inflammation can allow safe administration of HDMTX for most patients; indeed, this practice in Recife, Brazil, where methotrexate levels were not available, allowed for safe administration of hundreds of courses of HDMTX [60].…”
Section: Monitoring During Treatment With High-dose Methotrexatementioning
confidence: 99%
“…TLS is potentially fatal [11]. Also High-dose MTX is a major cause of toxicities as gastroenteritis, MTX encephalopathy [12,13].…”
Section: Discussionmentioning
confidence: 99%